Comparative study of the electron-atom and positron-atom bremsstrahlung - Yerokhin, Vladimir; Surzhykov, Andrey; Tashenov, Stanislav (Physical review. A, Atomic, molecular, and optical physics, 2012)
Fully relativistic treatment of the electron-atom and positron-atom bremsstrahlung is reported. The calculation is based on the partial-wave expansion of the Dirac scattering states in an external atomic field. A comparison of the electron and positron bremsstrahlung is presented for the single and double differential cross sections and the Stokes parameters of the emitted photon. It is demonstrated that the electron-positron symmetry of the bremsstrahlung spectra, which is nearly exact in the nonrelativistic regime, is to a large extent removed by the relativistic effects.
Published 19 September 2012
Gesehen am 27.06.2018